Solving one-dimensional unconstrained global optimization problem using parameter free filled function method - Ismail Bin Mohd; Yosza Dasril; Ridwan Pandiya; Herlina Napitupulu (Universitas Ahmad Dahlan, 2019)
It is generally known that almost all filled function methods for one-dimensional unconstrained global optimization problems have computational weaknesses. This paper introduces a relatively new parameter free filled function, which creates a non-ascending bridge from any local isolated minimizer to other first local isolated minimizer with lower or equal function value. The algorithm’s unprecedented function can be used to determine all extreme and inflection points between the two considered consecutive local isolated minimizers. The proposed method never fails to carry out its job. The results of the several testing examples have shown the capability and efficiency of this algorithm while at the same time, proving that the computational weaknesses of the filled function methods can be overcomed.